THE EFFECT OF STUDENTS' VOCABULARY MASTERY AND LANGUAGE ATTITUDES ON ENGLISH SPEAKING ABILITY SURVEY IN PRIVATE HIGH SCHOOLS IN BOGOR DISTRICT - Chamelia Asmarafuti; Soenarjati Djajanegara (Universitas Indraprasta PGRI, 2019)
The less ability to speak English of someone and the importance of mastering English, then it is necessary to develop effective and efficient in English learning so that mastery of English becomes better. Vocabulary mastery plays an important role because with a good vocabulary mastery, communication activities with others will be well established, In addition, the process of teaching and learning English is a reciprocal process between teacher and student to jointly seek the achievement of instructional goals. The process of teaching and learning English, especially students' speaking skills, not only results in increased student knowledge but also attitudes toward English that are more positive, and the way they learn changes more effectively and efficiently. Therefore, this thesis research was held as an effort to attain high scores as a form of student learning outcomes, with the results there is a significant influence of Vocabulary Mastery and Language Attitudes together on English Speaking Ability in Private High School in Bogor District, proved with Sig = 0.000 < 0,05 and Fcount = 10,408